Quantification of 3‐n‐butylphthalide in beagle plasma samples by supercritical fluid chromatography with triple quadruple mass spectrometry and its application to an oral bioavailability study. Issue 4 (7th January 2015) - Li, Yun; Zhao, Longshan; Li, Xiaoting; Guo, Bei; Zhao, Juanhang; Wang, Xianglin; Zhang, Tianhong
<x xml:space="preserve">Abstract</x> A high‐throughput, rapid, sensitive, environmentally friendly, and economical supercritical fluid chromatography with triple quadruple mass spectrometry method was established and validated for the first time to determine a cerebral stroke treatment drug named 3‐n‐butylphthalide in dog plasma. Plasma samples were prepared by protein precipitation with methanol and the analytes were eluted on an ACQUITY UPC2TM HSS‐C18 SB column (3 × 100 mm, 1.8 μm) maintained at 50°C. The mobile phase comprised supercritical carbon dioxide/methanol (90:10, v/v) at a flow rate of 1.5 mL/min, the compensation solvent was methanol at a flow rate of 0.2 mL/min and the total run time was 1.5 min per sample. The detection was carried out on a tandem mass spectrometer with an electrospray ionization source. Calibration curves were linear over the concentration range of 1.02–1021.00 ng/mL (r2 ≥ 0.993) with the lower limit of quantification of 1.02 ng/mL. The intra‐ and inter‐day precision values were below 15% and the accuracy was from 97.90 to 103.70% at all quality control levels. The method was suitable for a pharmacokinetic study of 3‐n‐butylphthalide in beagle dogs.